REGIONAL GOVERNMENT'S RESPONSIBILITY TO THE PROTECTION OF INDONESIAN WORKER EMPLOYED (TKIs) ABROAD (Review of Human Rights Perspective) - Lasatu, Asri (Tadulako University, 2017)
The purpose of the establishment of the Republic of Indonesia is to protect and realize the welfare of citizens. Therefore, the main responsibility of the government is to provide protection and guarantee to every citizen to get a job and a decent living for humanity. Limitations of domestic employment, as well as the public's desire to work overseas, should be responded positively by the government, by formulating regulations both at the central and regional levels. This study will examine the roles and responsibilities of local governments as an effort the law protection against Indonesian Migrant Worker working abroad.This research is a normative legal research with approach of legislation and concept approach and analyzed qualitatively to give perspective on legal issue to the object of this research study. The results show that the responsibility of local government, especially in the pre-placement, post-placement, and empowerment phase of placement of migrant workers, while the placement of migrant workers is the responsibility of the central government. Implementation of local government responsibilities should be supported by regulations established by local governments.